Coronary artery ectasia in post‐pericardiotomy syndrome. Issue 9 (6th August 2021) - Williams, Jason L.; Cua, Clifford L.; Stiver, Corey; Kovalchin, John P.; Lee, Simon
Abstract: Post‐pericardiotomy syndrome (PPS) is a common inflammatory process following cardiac surgery, in which the pericardial space was opened. Pericardial effusion (PE) is a common manifestation in PPS; however, coronary artery dilation is not associated with PPS. Inflammatory vasculitis in children are known to cause coronary dilation, in conditions such as in Kawasaki Disease (KD). We report a patient with PPS and concomitant coronary dilation by transthoracic echocardiography (TTE) following repair of her ventricular septal defect (VSD).